تصميم نظام ضبابي هرمي للتنبؤ بأداء الشبكات الكهربائية (Tishreen University, 2019)
The operating and development of electrical networks is a vital process in any electrical system, for its effect to the efficiency of service especially with the increased reliability and quality requirements. Where the network is monitored from the central control room to monitor any disturbances, and take the convenient procedures that keep working within the operating conditions. The more rapid and accurate the decision process, the higher the level of service and the network avoided more emergencies. Recently the concept prognosis is introduced to provide a previous evaluation of the risks to the network , and thus affect its reliability and quality of operation. In this research, we used fuzzy logic to build a hierarchical fuzzy performance prognosis algorithm that allows for the inclusion of additional factors that reflect the technical state of the element during its working period ,and processes it through a set of fuzzy controls that finally gives a prediction risk probability of the network based on income data. A graphical interface within Matlab environment representing the algorithm is achieved ,so it can be used on computers in the control centers to periodically predict contingencies in each update of data. A message is sent to the operator with the expected situation and the proposed action to correct them. يعد تشغيل واستثمار الشبكات الكهربائية عملية هامة جداً في أي منظومة كهربائية, لما له من أثر على كفاءة الخدمة خاصة مع زيادة متطلبات الموثوقية والجودة المرتبطة بتطور هذه الشبكات. تتم مراقبة الشبكة من غرفة التحكم المركزية لرصد أية تغيرات قد تؤثر على عملها, واتخاذ الإجراءات اللازمة التي تحافظ على العمل ضمن محددات التشغيل. فكلما كانت عملية اتخاذ القرار سريعة ودقيقة كلما رفعت سوية الخدمة وجنبت الشبكة المزيد من حالات الطوارئ. أدخل مؤخراً مفهوم التنبؤ بالأداء على عمليات التشغيل ليقدم تقييماً استباقياً لحالات المخاطر التي قد تهدد الشبكة وتؤثر بالتالي على موثوقيتها وجودة عملها. قمنا في هذا البحث باستخدام المنطق الضبابي لبناء خوارزمية للتنبؤ بالأداء تقوم على نظام ضبابي هرمي يسمح بتضمين بعض العوامل الإضافية التي تعكس الحالة الفنية للعنصر خلال فترة عمله, ويقوم بمعالجتها عبر مجموعة من المتحكمات الضبابية التي تعطي في النهاية توقعاً لاحتمال الخطر الذي قد يحدث على الشبكة بناء على معطيات الدخل. كما تم برمجة واجهة رسومية  ضمن بيئة ماتلاب تمثل الخوارزمية المذكورة بحيث يمكن استخدامها على الحواسيب في مراكز التحكم، للقيام بتقييم دوري لحالة الشبكة والتنبؤ بما قد يحدث من حالات طوارئ عند كل تحديث للبيانات وتظهر رسالة للمشغل بالحالة المتوقعة والإجراء المقترح لتداركها.